Telaah Kritis Pemikiran Clifford Geertz tentang Islam dan Budaya Jawa (Literature Review) - M. Fakhrul Irfan Syah; Abdul Muhid (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This paper discusses about Islam and Javanese culture in Clifford Geertz’s perspective. Geertz's thought was carried out in several stages. First, describing the meaning of religion according to anthropologists. Second, revealing the symbiotic side of Islamic and Javanese mutualism according to Geertz. Meanwhile, if seen from the appreciation and intensity of its practice of Islamic teachings, in the sociological construct, Muslims in Java can be classified into Santri, Abangan, and Priyayi. First is the representation of Javanese Muslims who are very strict in carrying out the teachings of Islam while, in contrast, second one and last is the Muslim community that carries out Islamic teachings in a perfunctory and often